2013
DOI: 10.1504/ijstl.2013.054190
|View full text |Cite
|
Sign up to set email alerts
|

Port hinterland intermodal container flow optimisation with green concerns: a literature review and research agenda

Abstract: Abstract:The closer link between ports and supply chain leads to a growing research area -port hinterland intermodal development. Focusing on the literature with mathematical models, the purpose of this paper is to categorise and analyse earlier research contributions on intermodal container flow optimisation, to identify the research trends and gaps, and to suggest future research directions. Results show that future research should focus on global intermodal container flow optimisation, addressing the approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 72 publications
0
55
0
3
Order By: Relevance
“…Similar research in terms of testing the bi-objective optimization minimizing cost and transit time conducted Lam, J. S. L. and Gu, Y., [7] observing import and export container flow to and from inland China. The results and analysis offer managerial insights of the impact of trade-offs between cost and transit time, and the effect of different carbon footprint requirements on transport planning.…”
Section: B Bi-objective Optimizationmentioning
confidence: 91%
See 1 more Smart Citation
“…Similar research in terms of testing the bi-objective optimization minimizing cost and transit time conducted Lam, J. S. L. and Gu, Y., [7] observing import and export container flow to and from inland China. The results and analysis offer managerial insights of the impact of trade-offs between cost and transit time, and the effect of different carbon footprint requirements on transport planning.…”
Section: B Bi-objective Optimizationmentioning
confidence: 91%
“…Studying literature data it was concluded that a small number of researchers investigated at the same time sea and land legs together [1], [7][8][9][10]. In most cases it is developed an optimization model which is based on the minimization for just one objective.…”
Section: A Single Objective Optimizationmentioning
confidence: 99%
“…The group of authors in paper [3] carried out a similar study, which involved testing the bi-objective optimisation, minimising cost and transit time, based on the import and export container flow to and from inland China. The analysis and final results provide managerial insights into the consequences of trade-offs between cost and transit time, and the effect of different carbon footprint needs on transport planning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studying literature data we conclude that a small number of researchers investigated at the same time see and land legs together [2,3,4]. In most cases it is developed an optimization model which is based on the minimization for just one objectivetransportation cost [5,6,7,8].…”
Section: Literature Reviewmentioning
confidence: 99%
“…[2] observing import and export container flow to and from inland China. The results and analysis offer managerial insights of the impact of trade-offs between cost and transit time, and the effect of different carbon footprint requirements on transport planning.…”
Section: Literature Reviewmentioning
confidence: 99%